Impact of the 2024 United States’ Presidential Election on the DJIA Index - Putra, Aditia Dwi; Fadli, Faishal (Contemporary Studies in Economic, Finance and Banking, 2025)
Major global political shifts, such as the United States Presidential Election, inevitably trigger waves of economic uncertainty worldwide. Because of this inherent volatility, it becomes absolutely essential for market participants to deeply understand how capital markets respond to such high-stakes events. This research is dedicated to examining the specific impact of the 2024 US Presidential Election on the major companies listed within the Dow Jones Industrial Average (DJIA). Focusing on two critical variables, which is Average Abnormal Return (AAR) and Average Trading Volume Activity (ATVA), this study adopts a quantitative event study methodology. By applying a Paired Sample t-Test, the research analyzes data across a specific observation window, comparing the 14 days immediately preceding the election against the 14 days following it. The analysis yields a compelling insight. There was a statistically significant shift in AAR values, there was no corresponding significant change in ATVA. This distinction highlights that the market’s reaction is primarily visible through price adjustments rather than spikes in transaction volume. Ultimately, this suggests that investors holding blue-chip stocks manage political risk strategically through efficient asset revaluation rather than engaging in impulsive trading, proving the market's resilience.